2023
DOI: 10.3390/ani13081282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity and Mutated PreS Analysis of Duck Hepatitis B Virus Recently Isolated from Ducks and Geese in China

Abstract: In this study, we detected 12 duck and 11 goose flocks that were positive for duck hepatitis B virus (DHBV) using polymerase chain reaction and isolated 23 strains between 2020 and 2022 in China. The complete genomes of goose strains E200801 and E210501 shared the highest identity (99.9%), whereas those of strains Y220217 and E210526 shared the lowest identity (91.39%). The phylogenetic tree constructed based on the genome sequences of these strains and reference strains was classified into three major cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Through the artificial challenging test over 72 days, the livers of ducks infected with G133E DHBV demonstrated acute injury such as enhanced periportal cell growth, massive hepatocytes lysis, and apoptosis compared with the ducks that were infected with wild-type DHBV; additionally, there were greater losses of mean body weights in the birds infected with G133E DHBV compared with the birds with wild-type DHBV [7]. In another study previously reported by our group, a total of 540 serum samples were collected from 23 duck farms and 31 goose farms in Central and Eastern China from 2020 to 2022, and the positive rates in duck and goose flocks reached 52.2% and 35.5%, respectively [8]. And a genome sequence analysis suggested that the 11 obtained geese-originated DHBV strains were all of the G133E type, and 5 of the 12 duck-originated strains were DHBV variants harboring the G133E mutation site in the preS protein, which further indicates that DHBV with increased virulence and transmission ability was highly prevalent in Chinese ducks, and even geese [8].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Through the artificial challenging test over 72 days, the livers of ducks infected with G133E DHBV demonstrated acute injury such as enhanced periportal cell growth, massive hepatocytes lysis, and apoptosis compared with the ducks that were infected with wild-type DHBV; additionally, there were greater losses of mean body weights in the birds infected with G133E DHBV compared with the birds with wild-type DHBV [7]. In another study previously reported by our group, a total of 540 serum samples were collected from 23 duck farms and 31 goose farms in Central and Eastern China from 2020 to 2022, and the positive rates in duck and goose flocks reached 52.2% and 35.5%, respectively [8]. And a genome sequence analysis suggested that the 11 obtained geese-originated DHBV strains were all of the G133E type, and 5 of the 12 duck-originated strains were DHBV variants harboring the G133E mutation site in the preS protein, which further indicates that DHBV with increased virulence and transmission ability was highly prevalent in Chinese ducks, and even geese [8].…”
Section: Introductionmentioning
confidence: 62%
“…In another study previously reported by our group, a total of 540 serum samples were collected from 23 duck farms and 31 goose farms in Central and Eastern China from 2020 to 2022, and the positive rates in duck and goose flocks reached 52.2% and 35.5%, respectively [8]. And a genome sequence analysis suggested that the 11 obtained geese-originated DHBV strains were all of the G133E type, and 5 of the 12 duck-originated strains were DHBV variants harboring the G133E mutation site in the preS protein, which further indicates that DHBV with increased virulence and transmission ability was highly prevalent in Chinese ducks, and even geese [8]. Even though there were no remarkable clinical symptoms, these findings imply that the health of ducks and geese was also influenced by DHBV infection, and the global poultry industry may suffer financial losses due to DHBV infection.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation